Effects of Lead on Hemopoeitic and Iron Status in Iraqi Workers at Lead Batteries Factory - Baghdad Science Journal (مجلة بغداد للعلوم)
The present study aimed to evaluate the effect of lead exposure on hemopoetic system (through the index delta-Aminolevulinic acid dehydratase ?-ALAD activity & hemoglobin concentration (Hb) ) and on iron status (levels of iron Fe, Ferritin Fr, Total iron binding capacity TIBC, percentage of transferine saturation TF%) in 44 Iraqi worker at lead batteries factory. Workers divided into two groups: smokers(n=21) mean aged (37.33±4.82 year)and non smokers(n=23) mean aged(40.78±7.89 year) and 45 healthy subjects mean aged (33.97±5.08)as control group . Activity of ?-ALAD ratio shows significant decrease (p ? 0.05) ,while Hb and hematocrit Hct were non significant (p ? 0.05) in smoker workers more than non smoker as compared to control . The results show a non significant decrease (p ? 0.05) in the sera levels of iron S.Fe, TS%, Fr in all workers as compared to control , the amount of decreasing for smoker more than non smoker except ferritin levels. A significant increases in the level of TIBC in workers as compared to control, this elevation is more in smoker than non smoker workers. In smoker workers, there was a significant positive correlation between the blood lead levels BLLs and Hb, Hct,TIBC whereas a significant negative correlation was observed between BLLs and S.Fe, TS%. In conclusion, the results of this study reveal the importance of monitoring the level of iron status in smoker peoples who dealing or exposure to lead due to the probability injured with anemia and used ?-ALAD ratio to predict the efficiency of their heme synthesis as a new marker for the diagnosis of early stage of anemia.